Bone bruising severity after anterior cruciate ligament rupture predicts elevation of chemokine MCP‐1 associated with osteoarthritis - Lukas G. Keil; Douglas S. Onuscheck; Lincoln F. Pratson II; Ganesh V. Kamath; Robert A. Creighton; Daniel B. Nissman; Brian G. Pietrosimone; Jeffrey T. Spang (Journal of Experimental Orthopaedics)
Abstract Purpose Anterior cruciate ligament rupture is associated with characteristic bone contusions in approximately 80% of patients, and these have been correlated with higher pain scores. Bone bruising may indicate joint damage that increases inflammation and the likelihood of posttraumatic osteoarthritis. We sought to characterize the severity of bone bruising following acute anterior cruciate ligament injury and determine if it correlates with synovial fluid and serum levels of the proinflammatory chemokine monocyte chemoattractant protein‐1 associated with posttraumatic osteoarthritis. Methods This was a retrospective analysis of data collected prospectively from January 2014 through December 2016. All patients who sustained an acute ligament rupture were evaluated within 15 days of injury, obtained a magnetic resonance imaging study, and underwent bone‐patellar‐tendon‐bone autograft reconstruction were offered enrollment. The overall severity of bone bruising on magnetic resonance imaging was graded (sum of 0–3 grades in 13 sectors of the articular surfaces). Serum and synovial fluid levels of monocyte chemoattractant protein‐1 were measured within 14 days of injury, and serum levels were again measured 6 and 12 months following surgery. Separate univariate linear regression models were constructed to determine the association between monocyte chemoattractant protein‐1 and bone bruising severity at each time point. Results Forty‐eight subjects were included in this study. They had a mean age of 21.4 years and were 48% female. Median overall bone bruising severity was 5 (range 0–14). Severity of bone bruising correlated with higher synovial fluid concentrations of monocyte chemoattractant protein‐1 preoperatively (R2 = 0.18, p = 0.009) and with serum concentrations at 12 months post‐reconstruction (R2 = 0.12, p = 0.04). Conclusions The severity of bone bruising following anterior cruciate ligament rupture is associated with higher levels of the proinflammatory cytokine monocyte chemoattractant protein‐1 in synovial fluid acutely post‐injury and in serum 12‐months following anterior cruciate ligament reconstruction. This suggests that severe bone bruising on magnetic resonance imaging after ligament rupture may indicate increased risk for persistent joint inflammation and posttraumatic osteoarthritis. Level of evidence III ― retrospective cohort study.